Phänologisch-geländeklimatologische Untersuchungen in Schwedisch-Lappland - Müller, Hans-Martin (ERDKUNDE, 1977)
This article contains some results of a research journey to Swedish Lapland which was supported by the Deutsche Forschungsgemeinschaft. The aim of the investigations was to gain an insight into the differentiation of the local climate of the terrain by using and assessing phenological observations. These are based upon springtime development of the birches (Betula pubescens), which cover most parts of the research area. More than 200 sites were regularly surveyed phenologically. The processes of bud development and leaf spreading were differentiated into 13 stages. At each site at least 25 trees were used as a sample and associated with their specific stage of development. Their frequency distributions and their averages yielded a measure of the phenological stage of each site that could be treated statistically. Details of the phenological development could be investigated on a regularly controlled profile. A correlation with temperature sums showed a high degree of agreement: the phenological development was highly dependent on the weather. A reduction of the observation results to a specific stage of development, namely the opening of the buds, made possible the drawing of an isophane map, which shows the sites with regard to their being early or late. It was possible to show that the differentiation of the sites into development stages, and their time lag, was dependent on the weather as well. The phenological development showed a strong correlation with soil-climatological factors and wind exposition. The height of the warm slope zone depended on the valley topography. The most favourable area was never higher than 70 m above the valley bottom; in most profiles it lay considerably lower. Because of the growth sites and growth forms at the timber line the phenological development was very strongly determined by microclimatological influences.